Killing of Multi-Drug Resistant Staphylococcus Aurous Isolated from Women with Genital Tract Infection with Special Reference to Laser Photosensitization - Shaimaa N. Mizil (Journal of Global Pharma Technology, 2018)
Multi-Resistant Staphylococcus aureus(MRSA)were obtained from Al-Yarmook Hospital in Baghdad from women with urinary tract infection (UTI)and genital tract infection(GTI)after susceptibility test for 17 antibiotics we selected the (MRSA)isolates and detect the methicillin resistance gene(mecA),we investigate the best dye for photosensitization among the four dyes (methylin blue MB, crystal violate CV, toluidin blue TB and coomassie brilliant blue-G (CCB) that has the maximum absorption of the wave length of the red laser(635 nm),the most resistant isolate used in  laser photosensitization death time experiment with the selected dye( toluidin blue TB)as the best dye for photosensitization in different power density (12,24,40,60,80 and 100)mW/cm2 with different exposure time ,we found from the results that the percentage of survival cells decreased with the increasing the exposure time to laser light and the time of killing MRSA decrease when the power density increasing. This considers an alternative method to kill MRSA.Keywords: Multi-resistant S. aureus, photosensitization, Laser.